PENGEMBANGAN INDUSTRI PENGOLAHAN CAPTIKUS DIDESA TOKIN KECAMATAN MOTOLING TIMUR KABUPATEN MINAHASA SELATAN - Muntu, Romana; Poli, Ellen Eva; Ramadhan, Muhamad Isa; Maxi Tendean; Hermon Maurits Karwur (Jurnal Social Science, 2025)
The purpose of the study was to determine the development of the 'captikus' processing industry in Tokin Village. The research method was descriptive qualitative, data collection techniques were observation, documentation, interviews and tests as the main techniques. The sample was purposive sampling. The results of the study showed that: 1) Efforts made by 'Captiukus' managers in Tokin Village were as follows: follow technological developments, organize businesses, make business plans, determine product prices, provide good service, expand market networks, and minimize production costs. 2) Factors that support business development are: Business capital, Labor, Willingness to do business/motivation to do business, Availability of raw materials, Availability of consumers, Existence of business opportunities, and the government that grants permits. 3) Factors that inhibit the development of the 'Captikus' industry are: Small business capital, Business permit obstacles, Lack of product innovation, Human resources, Business and consumer access and 4) The impact of the 'captikus' management business on the socio-economic life of the population.